2020
DOI: 10.1177/0022146520952769
|View full text |Cite
|
Sign up to set email alerts
|

The Long Arm of Social Integration: Gender, Adolescent Social Networks, and Adult Depressive Symptom Trajectories

Abstract: Peer connections in adolescence shape mental health in ways that differ by gender. However, it is unclear whether this association has an enduring impact on life course mental health. Using growth models with survey data from the National Longitudinal Study of Adolescent to Adult Health (Add Health Waves I–IV, N = 13,821, 51% white, 49% male), we examine how two dimensions of social integration during adolescence—popularity and sociality—predict depressive symptom trajectories from adolescence to adulthood (ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 46 publications
1
14
1
Order By: Relevance
“…A longitudinal study among British adults has also confirmed a bidirectional relationship between social support and mental health and that the relationship varied over the life course [50]. Furthermore, low social integration among peers in adolescence has recently been shown to predict higher levels of depression among US adults [51], and systematic reviews have reported evidence linking low of social support, social isolation, and loneliness to mental health problems [25,52]. On the other hand, having trust in people, feeling safe in the community, and having social reciprocity has been identified as factors associated with lower risk of mental distress [53].…”
Section: Discussionmentioning
confidence: 86%
“…A longitudinal study among British adults has also confirmed a bidirectional relationship between social support and mental health and that the relationship varied over the life course [50]. Furthermore, low social integration among peers in adolescence has recently been shown to predict higher levels of depression among US adults [51], and systematic reviews have reported evidence linking low of social support, social isolation, and loneliness to mental health problems [25,52]. On the other hand, having trust in people, feeling safe in the community, and having social reciprocity has been identified as factors associated with lower risk of mental distress [53].…”
Section: Discussionmentioning
confidence: 86%
“…Peer relationship quality similarly predicts later relationship quality (Cook et al 2016). Popularity in the peer network as a teen also predicts depressive levels for young women across adolescence and into adulthood (Kamis and Copeland 2020). While these patterns suggest that experiences among adolescent peers can have lasting effects on mental health beyond adolescence, the developmental salience of peers may be limited to adolescence, so that associations between mental health and teen network position do not persist as youth age into the new roles, environments, and experiences of young adulthood.…”
Section: Adolescent Peers and Young Adult Mental Healthmentioning
confidence: 90%
“…Gender differences are widely discussed in studies of young migrants’ social integration, social mentality, and health ( Kamis and Copeland, 2020 ; Park et al, 2021 ). Existing studies have demonstrated that a consensus has yet to be reached about how gender differences impact the health of young migrants across national contexts.…”
Section: Literature Reviewmentioning
confidence: 99%